Stylistic Analysis of Sudanese Newspapers Headlines: (With Reference to "Sudan Vision" Headlines- 2018-2019) - Malka Elsadig Yaagoob; Hassan Mohammed Abdelaal Almoukashfi; Elsharifa Elbashir Mohammed (White Nile Journal for Studies and Research, 2021)
q The aim of this study is to identify and analyze the stylistic features of newspapers headlines in terms of graph logical, morphological, rhetorical, grammatical and syntactic features. The sample is ten headlines chosen from widely read Sudanese newspaper "Sudan Vision" issued in (2018-2019). The researchers have used secondary sources for data collection. A descriptive analytic method was used to conduct the study. The main findings can be summarized as follow: The most outstanding graph logical feature is that words are written in large bold type with different colors which have distinctive meaning. The morphological features are the use of proper nouns, abbreviations and blending. The rhetorical feature used in the headlines is alliteration. Analyses of grammatical and syntactic features reveal that simple present tense is used in most of the headlines. The common syntactic features are usage of noun phrase and verb phrase. Based on the findings the researchers recommend that readers should be aware of stylistic features of news headlines in order to understand their meaning and they suggest further study on news headlines rhetorical features